Pengaruh Penggunaan Mulsa Jerami Padi dan Dosis KCl terhadap Produktivitas Kedelai (Glycine max L. Merr.) Kultivar Dering-1 pada Musim Kemarau - Irwan, A.W.; Sunarto, T. (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Good environmental conditions and balanced fertilizer are factors that influence the soybean production process to obtain high crop yields. It is hoped that the use of rice straw mulch coupled with regulating the potassium dosage can create a good environment and the availability of sufficient and balanced nutrients for the growth of the Dering-1 cultivar soybean plants so that yields can increase. This research aims to determine the effect of the type of straw mulch and the dose of KCl fertilizer to increase the yield of the Dering-1 cultivar soybean. The research was carried out from August to November 2024 in Rancaekek Kencana Village, Bandung Regency with an altitude of around 700 meters above sea level. From August-October it is still dry, but at the end of October 2024 there will be rain although the intensity is still moderate. The research used a split plot design with three replications. The first factor is the dose of straw mulch consisting of three levels, namely without mulch, 2 tons/ha of rice straw and 4 tons/ha of rice straw. The second factor is the dose of KCl fertilizer consisting of four levels, namely 50 kg/ha KCl, 100 kg/ha KCl, 150 kg/ha KCl and 200 kg/ha KCl. Observations were made on the components of soybean yield and yield. The research results showed that there was an interaction between the dose of rice straw and the dose of KCl fertilizer on the number of pods per plant, seed weight per plant, harvest index and soybean yield per hectare, except for the weight of 100 grains per plant. The best treatment was a treatment dose of 4 tons/ha of rice straw and 150 kg/ha of KCl fertilizer, with a yield of 2.18 tons per hectare of dry beans with a water content of 14 percent.